PENINGKATAN HASIL BELAJAR DAN KEMANDIRIAN SISWA PADA MATA PELAJARAN IPA MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) KELAS 4 SD - Rusiana Kumala (ELEMENTARY SCHOOL JOURNAL PGSD FIP UNIMED, 2017)
ABSTRACTThis study aims to improve student learning outcomes and independence through cooperative learning model Think Pair Share (TPS). The method of this research is Classroom Action Research (PTK) which consists of two cycles starting with planning, implementation, observation and reflection. Collection of test and non test data. The results showed an increase in learning outcomes and independence. In cycle one average learning outcomes 75.62 completeness value 75% completeness score. In cycle 2 the average learning outcomes increased to 83.75, completeness value 91.6. The result of independence in cycle 1 indicates self-sufficiency "Enough" (75%), in cycle 2 shows independence "Very Good" (91.6%)Keywords: Learning Outcomes, Think Pair Share (TPS), Student                   Independence